Study the effects of bromothymol blue material on the optical properties for polystyrene (PS). - Baghdad Science Journal (مجلة بغداد للعلوم, 2013)
Films of pure polystyrene (ps) and doped by bromothymol blue material with percentages(4%) prepared by using casting technique in room temperature , the absorption and transmission spectra has been recorded in the wavelength rang (200-900)nm and calculated refractive index , reflectivity, real and imaginary parts of dielectric constant and extinction coefficient . this study has been done by recording the absorption and transmission spectra by using spectrophotometer .